2020
DOI: 10.1186/s12882-020-02112-0
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 nephrology compendium: AKI, CKD, ESKD and transplantation

Abstract: The pandemic of coronavirus disease 2019 (CoVID-19) has been an unprecedented period. The disease afflicts multiple organ systems, with acute kidney injury (AKI) a major complication in seriously ill patients. The incidence of AKI in patients with CoVID-19 is variable across numerous international studies, but the high incidence of AKI and its associated worse outcomes in the critical care setting are a consistent finding. A multitude of patterns and mechanisms of AKI have been elucidated, and novel strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 97 publications
(88 reference statements)
7
71
0
12
Order By: Relevance
“…In contrast, a study from UK reported that 5 out of 7 transplant recipients with COVID- 19 had severe infection requiring intensive care and 1 out of 7 died [ 13 ]. The differences in outcome from centres may reflect the differences in severity of COVID- 19 infection, the treatment strategies adopted and the duration of follow up [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study from UK reported that 5 out of 7 transplant recipients with COVID- 19 had severe infection requiring intensive care and 1 out of 7 died [ 13 ]. The differences in outcome from centres may reflect the differences in severity of COVID- 19 infection, the treatment strategies adopted and the duration of follow up [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As treatment with RDV and TCZ is not indicated in patients with eGFR <30 mL/min/1.73 m 2 and, in turn, the absence of such treatment may influence the investigated outcomes, we may overestimate the causal effect of CKD on study endpoints. Lastly, due to the lack of control laboratory tests during hospitalization in some patients, we performed analysis taking into consideration the baseline renal status of patients with CKD, not looking at the development of acute kidney injury (AKI) in the course of COVID-19 in those individuals, although the experience from previous reports showed that AKI is associated with higher mortality [ 24 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for AKI in critical patients with COVID-19 vary according to the population. Older age, male gender, black race, obesity, diabetes, hypertension, heart failure, chronic kidney disease, leukocytosis, anemia, lymphopenia, increase in levels of serum inflammatory markers (D-dimer, PCR, and IL-6), and need for mechanical ventilation and vasoactive drugs as well as the use of angiotensin-converting enzyme inhibitors were associated with a higher risk of AKI development in COVID-19 critical patients (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Herein, chronic kidney disease was more frequent in patients who developed AKI (18.5 vs. 14.6%), however with no statistical significance.…”
Section: Discussionmentioning
confidence: 99%